Inclusão escolar e a atuação dos professores de deficientes mentais do Estado de São Paulo - Petrechen, Eli de Haro (Universidade Federal de São Carlos, 2006)
From the directive and national education basis law approved in 1996 the lawful instrument was granted in order to break the school exclusion ideology. Within this context the special education should serve a brand new purpose, developing the inclusive character proposal. In order to adapt to the new paradigm, federal and state institutions organized and set the goals for the organization and orientation for the special student based on the inclusion proposition. In 2000 the Govern of the state of São Paulo restated and defined its teaching system as inclusive, purposing new attributions to the special education teacher as an active participation in the school teaching program to provide orientation on the formation and inclusion of the special needs students in the regular schools. The special education teachers specially those specialized in the mental retardation, from the state public school net are the subjects of this research that aimed to investigate the changes of the performance of the school inclusion politics of such state, as well as to set the profiles of its teachers. A questionnaire was sent through regular mail to 300 teachers who work at the Specialized Pedagogic Support Services (SAPS) in order to get the data from the resources or special classes from the mental disabled students within the Teaching Coordination for the Interior (CEI) and 61 regional head offices and by the Teaching Coordination of São Paulo Metropolitan Region (COGSP) with 17 head offices. 41 forms returned, being 39 fully completed and two without marks. The forms covered 26 counties form 22 regional head offices. We were able to show in a described way the collected data. The results indicated that in the last five years, after the approval of the resolution 95/00, some significant changes happened to the special education net and the most significant ones according to the teachers were the opening of research rooms, the extinction of special classes, the exempt of medical and psychological decisions and the necessity of the pedagogic evaluation for the students direction for the specialized service. As a consequence of the changes some teachers that acted in the Special Classes, that were not effective, were released, the effective ones were redistributed to other school units. The students of the disabled classes, were redistributed to the common classes, or to special schools or to other school units that remained the special classes, the process implementation presented different nuances, however not very significant, because the guidelines and the ordination of the actions result from the same General office of Education (GOE). The conclusion of the study is that the changes are happening, however the evidences point that they are unilateral actions, without effective and active participation of the specialized teacher staff, and that they are not bringing the necessary changes in the teachers' performance and consequently, they are not contributing nor for the teaching quality nor for the students' permanence with mental retardation in the common class or in the regular teaching. The teachers make many suggestions for the process that they could be considered.
Keywords: Educação especial; Inclusão escolar; Deficiência mental; Escola pública; Prática docente; São Paulo (Estado); School inclusion; Special education teachers; Mental disabled; Paulista state net; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL